Enhanced discrimination of normal oocytes using optically induced pulling-up dielectrophoretic force - Hwang, Hyundoo; Lee, Do-Hyun; Choi, Wonjae; Park, Je-Kyun (Biomicrofluidics, 2009)
We present a method to discriminate normal oocytes in an optoelectrofluidic platform based on the optically induced positive dielectrophoresis (DEP) for in vitro fertilization. By combining the gravity with a pulling-up DEP force that is induced by dynamic image projected from a liquid crystal display, the discrimination performance could be enhanced due to the reduction in friction force acting on the oocytes that are relatively large and heavy cells being affected by the gravity field. The voltage condition of 10 V bias at 1 MHz was applied for moving normal oocytes. The increased difference of moving velocity between normal and starved abnormal oocytes allows us to discriminate the normal ones spontaneously under the moving image pattern. This approach can be useful to develop an automatic and interactive selection tool of fertilizable oocytes.